Relationship of Oxidative Stress as a Link between Diabetes Mellitus and Major Depressive Disorder - Réus, Gislaine Z. (Oxid Med Cell Longev, 2019)
Both conditions, major depressive disorder (MDD) and diabetes mellitus (DM) are chronic and disabling diseases that affect a very significant percentage of the world's population. Studies have been shown that patients with DM are more susceptible to develop depression, when compared to the general population. The opposite also happens; MDD could be a risk factor for DM development. Some mechanisms have been proposed to explain the pathophysiological mechanisms involved with these conditions, such as excess of glucocorticoids, hyperglycemia, insulin resistance, and inflammation. These processes can lead to an increase in damage to biomolecules and a decrease in antioxidant defense capacity, leading to oxidative stress.